Value stream mapping – a tool to detect and reduce waste for a lean manufacturing system - Noraini, Mohd Razali; Mohd Nizam A., Rahman (Springer, Singapore, 2020)
Waste is a non-value added activity that may exist everywhere in the production line. This waste is an activity that consumes resources but does not directly contribute to product or service and does not add value to the customer. This paper presents the classification of waste and the steps to implement value stream mapping (VSM) which is one of the powerful lean practice to detect and analyze waste activities in the manufacturing operation.